INTRODUKSI PANGAN ALTERNATIF BERNUTRISI “NUGGET JANTUNG PISANG” DI DESA CIBODAS KECAMATAN BANJAR KABUPATEN PANDEGLANG - Yeni Widyastuti (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
The goal of SDG's 1 is poverty alleviation and the goal of SDG's 2 is to end hunger. The achievement of these two targets is carried out through strengthening food security at the individual level, improving nutrition and public health, and reforming the agricultural system towards a more resilient and sustainable direction. An indicator of achieving this goal is if everyone, including the poor and those in vulnerable conditions, including pregnant women, babies, the elderly, and people with disabilities, has access to diverse, nutritious, balanced, safe, and sufficient food throughout the year, to be able to live a healthy, intelligent, active, and productive life. Food diversification is an integral part of food security both in terms of food availability, accessibility and feasibility. Banana hearts contain vitamins that are beneficial for human health such as vitamin A, B vitamins, vitamin C and contain energy, carbohydrates and fats that are beneficial for the body. The introduction of nutritious alternative foods in the form of banana heart nuggets can be an easy, cheap and affordable food alternative for the community. Keywords: Alternative Food; Heart of Banana; Nutrition